Respuesta :
5 - 2 = 3
3 - 14 = -11
-11 = (-2) - 7
-11 = -9
-11 ≠ -9
this equation is false
hope this helps
3 - 14 = -11
-11 = (-2) - 7
-11 = -9
-11 ≠ -9
this equation is false
hope this helps
Hey there!
We'll first clear up all the signs. If you're adding a negative, you're just subtracting. Therefore, we have:
5 - 2 - 14 = -2-7
Clear up left side:
-21 = -2-7
Simplify right side to get:
-21 = -9
However, this isn't a true statement. If there was a missing variable, let me know and I'd be happy to help you.
We'll first clear up all the signs. If you're adding a negative, you're just subtracting. Therefore, we have:
5 - 2 - 14 = -2-7
Clear up left side:
-21 = -2-7
Simplify right side to get:
-21 = -9
However, this isn't a true statement. If there was a missing variable, let me know and I'd be happy to help you.